2012
DOI: 10.1111/j.1477-2574.2011.00417.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of surgical site infection after liver resection: a multicentre analysis using National Surgical Quality Improvement Program data

Abstract: These findings may contribute towards the identification of patients at risk for SSI and the development of strategies to reduce the incidence of SSI and subsequent costs after liver resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 26 publications
6
79
1
5
Order By: Relevance
“…[6]. In addition to our prior work, multiple other studies have confirmed the impact of nutritional status and endogenous patient risk factors on surgical morbidity in general [7][8][9]. While many factors such as age, performance status, frailty and nutrition can be determined prior to surgery, tumor dissemination (and thus extent of surgery required for complete cytoreduction) is more difficult to assess preoperatively.…”
Section: Introductionsupporting
confidence: 57%
“…[6]. In addition to our prior work, multiple other studies have confirmed the impact of nutritional status and endogenous patient risk factors on surgical morbidity in general [7][8][9]. While many factors such as age, performance status, frailty and nutrition can be determined prior to surgery, tumor dissemination (and thus extent of surgery required for complete cytoreduction) is more difficult to assess preoperatively.…”
Section: Introductionsupporting
confidence: 57%
“…In the literature review [2,5,6,8,[15][16][17][18][19] (Table 5), we found that studies conducted in Asian countries showed low rates of incisional SSI compared with those conducted in Europe or America. By contrast, the incidences of organ/space SSIs were similar between these regions.…”
Section: Systematic Literature Reviewmentioning
confidence: 97%
“…After hepatectomy, bile leakage, ascites, and surgical site infection (SSI) are the main causes of major postoperative morbidity [2][3][4]. The incidence of SSIs after hepatectomy has been reported to be 3.1-14% [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between SSI and sex has shown conflicting results. One study found that SSI is more common in male patients (p < 0.001) 9 , whereas another found that it was more common in female patients (p = 0.000) 11 . Gastrointestinal surgeries exhibited differences in the development of SSI.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, other risk factors for SSI were observed, namely intraoperative transfusion of blood components, surgical reinterventions, and African or mixed ethnicity. Blood transfusion causes patient's immunosuppression, which may have increased the likelihood of developing SSI [8][9][10] . Reintervention may be a risk factor due to additional handling of the surgical site, favoring the colonization and carrying of microorganisms to the surgical site 10 .…”
Section: Discussionmentioning
confidence: 99%